HUMAN PSYCHOLOGY AND PRAGMATONYMS - S.М. Akhmadaliyeva; N.Z.Shavkatova (Ta'lim innovatsiyasi va integratsiyasi, 2024)
In world linguistics, several new directions of anthropocentric paradigm such as sociolinguistic, linguocultural, pragmatic, psycholinguistic, neurolinguistic have emerged. Currently, the study of pragmatonyms among all units of the onomastic scale based on a new paradigm is on the agenda. Therefore, analyzing the linguistic, cultural and socio-linguistic features of pragmatonyms provides important information about the national-cultural identity of the people, the national way of seeing the world, religious-mythological views, traditions, values, and social-political life. it acquires a special scientific and theoretical importance in learning and illuminating the gradual improvement of the language. Within the framework of Uzbek onomastics, pragmatonyms have not been specially collected and monographically researched. Researching all pragmatonyms that are currently in practice on the basis of the achievements of modern linguistics is one of the urgent tasks. Because "paying attention to our mother tongue, which is the symbol of our national identity, the basis of our spirituality will be further strengthened ". In this sense, research, classification and description of lexical-semantic, nominative-motivational, etymological, derivational, structural, sociolinguistic and linguocultural characteristics of pragmatonyms, and on this basis, enriching Uzbek onomastics with scientific- theoretical views and practical interpretations of pragmatonyms is in front of the field and one of the important tasks.